The first cars - Baxter, Roberta 1952- (North Mankato, Minnesota Capstone Press, 2015)
"Large photographs and simple text describe eight early cars"--
Cars of yesterday -- Electric cars -- Gasoline cars -- Car racing -- Cars for everyone -- The first indy 500 -- The first muscle car
The world around us (transportations)
Includes bibliographical references and index
1 2 13
NEW_ZTN_GN
Keywords: Automobiles -- Juvenile literature; Automobiles -- History -- Juvenile literature